MICROCONTROLLER-BASED VEHICLE TESTING UNITS: ALTERNATIVE SPEED MEASUREMENT TOOLS IN SPEEDOMETER TESTING - Wibowo, Helmi; Laksana2, Tri Adi; Srianto, Srianto (Teknik Elektro Universitas Siliwangi, 2024)
The use of the Speedometer Tester test equipment that is currently available has not been fully implemented in motorizedvehicle testing units. One of the causes is the test equipment which is constrained due to damage caused by long -term use.This research discusses the design of microcontroller-based speed measuring devices as an alternative to the use of testequipment in speedometer testing when problems occur in the form of damage to the test equipment in the Motor VehicleTesting Unit. This type of research is development or Research and Development (RD) which aims to produce new productsor improve existing products. Design of a Microcontroller-Based Speed Measuring Device consisting of an input, namely anInfared Proxlimity Sensor, then an Arduino process control with an LCD output connected to a Thermal Print er which canprint measurement results. Based on the test results of the design tool for speed measuring devices on microcontroller -basedmotorized vehicle testing units, an average success rate of 97.9% was obtained, and an average deviation of 2.1%. Thedesign performance of a microcontroller-based speed measuring device can function according to the program designed.